Health promotion actions on suicide in Campo Grande county/MS: experience report (Research, Society and Development, 2020)
Suicide is the intentional act of the individual to put an end to his life, being currently considered a public health problem that involves several sociocultural, historical, psychosocial and environmental factors. This study aims, based on the use of educational strategies, to disseminate preventive information about suicide, emphasizing people's awareness of the impact of this act. This is an experience report with a descriptive approach, which took place in Campo Grande, capital of Mato Grosso do Sul State, Brazil. The actions were carried out in public places, from the distribution of pamphlets, conversation with the population, theater play, round table, classroom course, to the realization of lectures and conversation circles. Professors, technicians and students from several higher education courses at the State University of Mato Grosso do Sul developed all actions, targeted to the general population. The health education strategies developed reached 5,758 people, allowing the reporting of different experiences and enabling people to reflect and share their attitudes, behaviors and feelings, such as impotence, suffering and emotional vulnerability of those involved. Therefore, the implementation of educational activities that promote mental health and open spaces for the population to discuss suicide should be encouraged, as well as new studies and research to strengthen the capacity to develop public policies.